3D-Printed Plasmonic Nanocomposites: VAT Photopolymerization for Photothermal-Controlled Drug Release - Torres Fredes, Ignacia Paz (2024)
Background: Gold nanoparticles can generate heat upon exposure to radiation due to their plasmonic properties, which depend on particle size and shape. This enables precise control over the release of active substances from polymeric pharmaceutical formulations, minimizing side effects and premature release. The technology of 3D printing, especially vat photopolymerization, is valuable for integrating nanoparticles into complex formulations. Method: This study aimed to incorporate gold nanospheres (AuNSs) and nanorods (AuNRs) into polymeric matrices using vat photopolymerization, allowing for controlled drug release with exposure to 532 nm and 1064 nm wavelengths. Results: The AuNSs (27 nm) responded to 532 nm and the NRs (60 nm length, 10 nm width) responded to 1064 nm. Niclosamide was used as the drug model. Ternary blends of Polyethylene Glycol Diacrylate 250 (PEGDA 250), Polyethylene Glycol 400 (PEG 400), and water were optimized using DesignExpert 11 software for controlled drug release upon specific wavelength exposure. Three matrices, selected based on solubility and printability, underwent rigorous characterization. Two materials achieved controlled drug release with specific wavelengths. Bilayer devices combining AuNSs and AuNRs demonstrated selective drug release based on irradiation wavelength. Conclusions: A pharmaceutical device was developed, capable of controlling drug release upon irradiation, with potential applications in treatments requiring delayed administration.